Treating Vulnerable Consumers ‘Fairly’ When They Make a Complaint About Banking or Finance in Australia - Tania Sourdin; Mirella Atherton (Bond Law Review)
The Australian Financial Services Reform Act 2001 (Cth) requires that licenced banking and financial services providers establish internal dispute resolution (‘IDR’) systems complying with requirements promulgated by the Australian Securities and Investments Commission (‘ASIC’). In addition, licence holders are required to be members of an ASIC approved External Dispute Resolution (‘EDR’) scheme so that if a complaint is not resolved following the use of internal mechanisms, an external dispute resolution facility is available for most banking consumers. In late 2018, a new EDR body was established, the Australian Financial Complaints Authority (‘AFCA’), to deal with external complaints. The 2018 Royal Commission into the banking and finance sector uncovered significant issues in terms of the banking and financial sector and raised a number of serious concerns that were largely linked to how consumers contracted with banks and other organisations however information about existing complaint handling arrangements was limited. In particular, there was little demographic information about consumers who use IDR and EDR arrangements or what factors may be relevant in terms of the settlement of complaints and disputes. In this regard, currently sections 912A(1)(g), (2) of the Corporations Act direct the form of AFSL holders’ IDR and EDR systems, but they do not impose any obligations on AFSL holders in terms of conduct when providing the systems. In terms of consumers more generally, it is unclear how many consumers could be classified as ‘vulnerable’ and may settle a dispute on less favourable terms because the impact of proceeding may place them in an even more disadvantageous position. It is suggested that better reporting in relation to IDR and EDR activity together with targeted independent advocacy services and training of relevant staff in respect of the Australian Consumer Law could assist consumers and enable more effective reporting of misconduct issues.